1979
DOI: 10.1126/science.204.4388.62
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Analysis of Zooplankton Spatial Heterogeneity

Abstract: Continuous estimates were obtained of zooplankton abundance, chlorophyll fluorescence, and water temperature along 10-to 100-kilometer transects of the North Sea. Spectral analysis methods were applied to the data. The "patchiness" of the plankton was distributed over all the length scales resolved with no indication of a characteristic patch size. The relative intensity of the zooplankton patchiness was greater than that of the phytoplankton at all spatial scales, with this difference becoming progressively g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(82 citation statements)
references
References 7 publications
6
74
1
1
Order By: Relevance
“…This lack of correspondence between export flux and NPP may also be caused by spatial variability in export that operates on smaller spatial scales than that for phytoplankton pigment concentrations or NPP. Evidence of this can be found in the literature (e.g., Mackas and Boyd, 1979;Abraham, 1998) assuming that 234 Th scavenging and particle export flux varies on the same spatial scales as zooplankton abundance in the euphotic zone. This is conceivable as zooplankton create export through their production of fecal pellets and as the packagers of marine snow (e.g., Alldredge and Silver, 1988).…”
Section: Variability In Particle Flux and Attenuationmentioning
confidence: 79%
See 1 more Smart Citation
“…This lack of correspondence between export flux and NPP may also be caused by spatial variability in export that operates on smaller spatial scales than that for phytoplankton pigment concentrations or NPP. Evidence of this can be found in the literature (e.g., Mackas and Boyd, 1979;Abraham, 1998) assuming that 234 Th scavenging and particle export flux varies on the same spatial scales as zooplankton abundance in the euphotic zone. This is conceivable as zooplankton create export through their production of fecal pellets and as the packagers of marine snow (e.g., Alldredge and Silver, 1988).…”
Section: Variability In Particle Flux and Attenuationmentioning
confidence: 79%
“…This is conceivable as zooplankton create export through their production of fecal pellets and as the packagers of marine snow (e.g., Alldredge and Silver, 1988). Observations and numerical experiments generally show power spectra for phytoplankton abundance that have redder (steeper) wavenumber spectra than do zooplankton distributions (e.g., Mackas and Boyd, 1979;Tsuda et al, 1993;Abraham, 1998 -though counter examples have been discussed by Martin and Srokosz, 2002). This means that more of the variance in phytoplankton concentrations is contained on larger scales than for zooplankton abundances and presumably for export and 234 Th flux.…”
Section: Variability In Particle Flux and Attenuationmentioning
confidence: 99%
“…Seabirds forage in an environment where physical processes depend on scale (Stommel 1963) and where biological and physical processes interact to impart scale-dependent spatial structure to planktonic biomass (Platt 1972, Mackas & Boyd 1979. Scaledependent response by birds to hydrographic structuring of marine ecosystems is suggested by the fact that bird aggregations on the order of 10 to 50 km in lateral extent have been reported along transects normal to hydrographic features in the California Current (Briggs et al 1984) and in the Bering Sea (Schneider 1982, Kinder et al 1983, Woodby 1984.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented zooplankton-phytoplankton interactions through correlation analysis, but the trophic consequences of such interactions were not quantified (Mackas and Boyd 1979;Star and Mullin 1981;Malone and McQueen 1983). Studies have also shown that zooplankton spatial patterns can differ depending on body size (Martin and Srokosz 2002), especially if these patterns are wind-driven (Blukacz et al 2009).…”
Section: Discussionmentioning
confidence: 99%